Rethinking the Form and Function of Cities in Post-Soviet Countries - Coulibaly, Souleymane (World Bank, Washington, DC, 2013)
Eurasian cities, unique in the global spatial landscape, were part of the world's largest experiment in urban development. The challenges they now face because of their history offer valuable lessons to urban planners and policymakers across the world from places that are still urbanizing to those already urbanized. Today, Eurasian cities must respond to three big changes: the breakup of the Soviet Union, the return of the market as the driving force of society, and the emergence of regional powers such as the European Union, China, and India that are competing with the Russian Federation for markets and influence in its former satellites. Several methods of analysis indicate an imbalance across Eurasia, implying a need to readjust Eurasia's urban structure. National policies in Eurasia are still preoccupied with spatial equity. But the concentration of economic activity in large cities is fundamental to national competitive advantage: they foster innovation through their diversity of industries -- and reduce production costs through their economies of scale. This paper suggests some ideas on how policymakers can harness the economic power of cities to drive national economic development, by focusing on four themes: planning, connecting, greening, and financing cities.